1996
DOI: 10.1073/pnas.93.9.3984
|View full text |Cite
|
Sign up to set email alerts
|

The ALIAmide palmitoylethanolamide and cannabinoids, but not anandamide, are protective in a delayed postglutamate paradigm of excitotoxic death in cerebellar granule neurons.

Abstract: The amino acid L-glutamate is a neurotransmitter that mediates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
209
2
17

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(240 citation statements)
references
References 47 publications
12
209
2
17
Order By: Relevance
“…In contrast, other studies using ISH and radioligand binding assays detected CB 2 mRNA and receptor binding in rat retina (7), mouse cerebral cortex (8), and hippocampus and striatum of nonhuman primates (9). More recent studies using RT-PCR also detected CB 2 mRNA in the cortex, striatum, hippocampus, amygdala, and brainstem (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 79%
“…In contrast, other studies using ISH and radioligand binding assays detected CB 2 mRNA and receptor binding in rat retina (7), mouse cerebral cortex (8), and hippocampus and striatum of nonhuman primates (9). More recent studies using RT-PCR also detected CB 2 mRNA in the cortex, striatum, hippocampus, amygdala, and brainstem (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 79%
“…Anandamide (arachidonoylethanolamide, AEA) and its analogue palmitoylethanolamide (PEA) regulate many of the same pathophysiological processes, including pain perception, convulsions, neurotoxicity and inflammation (Calignano et al 1998;Lo Verme et al 2005;Jaggar et al 1998;Lambert et al 2001;Skaper et al 1996). They both fulfill the three criteria required to be considered bona fide lipid transmitters: stimulus-dependent production, interaction with specific receptors and enzymatic inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…N-Palmitoylethanolamine has anti-inflammatory (13)(14)(15), anti-nociceptive (16,17), immunosuppressive (18), neuroprotective (19), and antioxidant (20) effects. Recently, it was shown that the anti-inflammatory action of N-palmitoylethanolamine could be mediated by the activation of peroxisome proliferator-activated receptor-␣ (PPAR-␣) (21).…”
mentioning
confidence: 99%